NATO Persistence and Expansion: Case Study of the Republic of North Macedonia - Jamabo, Ivy Otonye Mcwilson (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The origin of the North Atlantic Treaty Organization (NATO) can be found in its members perceived need to balance rising Soviet power in the aftermath of World War II, however, the breakdown of Soviet rule in the late 1980s did not prompt NATO's collapse. Many scholars expected NATO to fade out after the soviet threat disappeared nut NATO continues to persist and even expand in membership, function and structure. The purpose of this thesis therefore, is to analyse the possible reasons for NATO‘s persistence, and the factors that make it attractive to new members in the Post-Cold War era. In this dissertation, it will be argued that NATO persists and expands owing to the fact that, it balances the resurfaced Russian threat, given there exist, the fear of unknown threat, which can be from any country especially with the increase in nuclear activities, also, NATO continues to make itself attractive and relevant by carrying out certain key internal alliance and eternal functions for and on behalf of its allies, lastly there are no feasible alternatives to NATO therefore, considering the cost of establishing one, will lead to the appreciation and growth.

ÖZ: Kuzey Atlantik Antlaşması Örgütü'nün (NATO) kökeni, örgüt üyelerinin II. Dünya Savaşı sonrasında yükselen Sovyet iktidarını dengeleme ihtiyacına dayanır, ancak 1980'lerin sonunda Sovyet yönetiminin yıkılması NATO‘nun çöküşüne yol açmadı. Birçok bilim adamı NATO‘nun Sovyet tehdidinin ortadan kalkmasından sonra NATO‘nun varlığını sürdüremeyeceğini bekliyordu. Ancak, NATO üyeliğini, işlevini ve yapısını devam ettirmeye ve hatta genişletmeye devam ediyor. Bu tezin amacı, bu nedenle, NATO'nun sürekliliğinin olası nedenlerini ve onu Soğuk Savaş sonrası dönemde yeni üyelere çekici kılan faktörleri analiz etmektir. Bu tezde, NATO‘nun mecvut olmaya ve genişlemeye devam edeceği tartışılacaktır, çünkü var olan Rus tehdidinin, nükleer faaliyetlerin artmasıyla herhangi bir ülkeden gelebilecek bilinmeyen tehdit korkusunun yeniden ortaya çıkması halinde dengelenmesine hizmet ediyor. Ayrıca, NATO, iç-ittifaklar ve ebedi işlevleri yerine getirerek kendisini çekici ve ilgili kılmaya devam ediyor, son olarak NATO‘ya uygulanabilir alternatifler bulunmuyor, bu nedenle, birisinin kurulmasının maliyeti göz önüne alındığında, takdir edilmeye yol açacak.
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2019. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Political Science and International Relations Department; North Atlantic Treaty Organization (NATO)--Expansion; Macedonia--Politics and government--NATO Membership; North Atlantic Treaty Oganisation; Expansion; Persistence; Post-Cold War